Enhancing the activities of small business enterprises for poverty alleviation - Djalilova Shaxlo Ismoiljon kizi, (THE INNOVATION ECONOMY, 2026)
This study examines methods for improving the operations of small business enterprises (SBEs) as an essential means of alleviating poverty. Acknowledging the crucial contribution of SBEs to job creation, income generation, and local economic growth, this research explores the primary factors that limit their effectiveness in reducing poverty. The study evaluates policy measures, access to financing, skills training initiatives, and technological adoption as potential ways to enhance their impact. By pinpointing best practices and tackling the obstacles faced by SBEs, this research intends to offer practical recommendations for policymakers and practitioners aiming to harness the potential of small businesses to elevate communities and lower poverty rates.